Population based study of obesity in Turkey: results of the Turkey Nutrition and Health Survey (TNHS)-2010 - Pekcan, Ayla Gülden; Samur, Gülhan; Dikmen, Derya; Kızıl, Mevlüde; Rakıcıoğlu, Neslişah; Yıldız, Emine Akal; Özel, Hülya Gökmen; Mercanlıgil, Seyit Mehmet; Ersoy, Gülgün; Karaağaoğlu, Nilgün; Aksoy, Burcu; Yılmaz, Damla; et al. (Progress in Nutrition, 2017)
Aim: The objective of this paper is to present a baseline data on the national prevalence and distribution of overweight and obesity in adults, derived from the results of Turkey National Nutrition and Health Survey (TNHS)-2010. Methods: Prevalence data for adults (9820 adults, aged 19–65 years) were the customised data from the nationally representative National Nutrition and Health Survey (2010). Body weight, height, waist and hip circumferences were measured and body mass index (BMI), waist to hip ratio were calculated. BMI (weight-kg/height-m2), waist circumference (cm) and waist to hip ratio were classified and evaluated according to WHO criteria and recommendations. Results:  Mean BMI for all age groups were 26.4±4.5 kg /m2 in men and 28.9±6.4 kg/m2 in women. Overall, prevalence of overweight and obese adults were 34.6% (39.1% in men, 29.7% in women) and 30.3% (20.5% in men, 41.0% in women) respectively.  While the adults aged 51–64 years old were more likely to be obese (30.7% in men and 64.4% in women), adults aged 65 years and over were found to be more overweight (46.0% in men and 30.4% in women). High waist circumference and high waist-to-hip ratio were identified as 24.8% and 54.2% in men, as 53.9% and 40.4% in women, respectively. Conclusions: Obesity and overweight are major public health problems in Turkey. Preventive public measures have started to be implemented by the Turkish government and other bodies to control the increasing trends in obesity.